DEVELOPING ISLAMIC-BASED MANDARIN CONSTRUCTIVIST TEACHING MATERIALS - Mukarramah Mukarramah (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2022)
This research is motivated by the absence of Mandarin language teaching materials that are integrated with Islamic values in their learning and the use of Mandarin language teaching materials, especially textbooks from the country of origin of China (People's Republic of China) which is still thick with eastern culture and less relevant to Islamic values. The research stages are identification analysis, formulation of teaching materials, readability test, trial, validation, and revision as well as making a final prototype. This research concludes that (1) Islamic-based Mandarin constructivist teaching materials are needed, especially in Islamic educational units that include Mandarin in their curriculum. (2) The design of teaching materials with the main topics of discussion on prayer, fasting and Eid has gone through the trial, validation and revision stage to produce the product is in the form of an Islamic-based constructivist Mandarin textbooks for beginners consisting of a teacher's manual and a student's book. (3) Based on the results of the readability test and validation of material experts, Islamic-based Mandarin teaching materials have been feasible 4) Islamic-based Mandarin Language Teaching Materials have received good acceptability from teachers and students as users.